Um modelo econométrico para a probabilidade subjetiva de sofrer violência doméstica em Fortaleza, Brasil - Farias, Pedro Phillipp Moreira de (2016)
This work aims to build an econometric model of women’s subjective probability of Fortaleza to be victims of domestic violence, identifying determinant factors of this subjective probability and analyzing how these determinants influence the subjective expectation of them. It was developed with socioeconomic data and expectations and victimization experiences of these women drawn from a database of more than 4000 residents of Fortaleza in 2011. As the dependent variable, we used the subjective probability (ranging from 0 to 100%) indicated by the interviewed when asked her what chance she considered to be a victim of domestic violence in the next 12 months. Two econometric models were estimated: tobit e double-hurdle. By tobit model, it was found that the variable indicating whether the woman had previously suffered domestic violence showed positive influence on the dependent variable, revealing that the trauma has already been victimized, the fear of being a victim again, and the incorporation of a more submissive to partner behavior make women indicate higher probabilities. The dummy indicating if she already was at least in her second marriage also showed influence positive, revealing that the occurrence of possible friction between the current and previous partner(s) makes the woman has more perception of risk. The other variable that showed influence positive was the dummy indicated that if she received the Bolsa Familia resources, suggesting, as a part of the literature, that the transfer of resources for women would increase their bargaining power within the household, generating an increase in the level of conflict with the partner for control of resources. The household income variable diminished the perception of woman’s risk as suggested by the literature, which constantly connects poverty to family violence. Finally, also found the purely physical influence: taller women that their partners have perceived lower risk. By the double-hurdle model, it was found that the fact that she has suffered domestic violence previously made to increase the chance to respond with positive probability of being a victim and increased the value of this probability if she really responded with positive probability. Conversely, it was found that the woman’s height from the man increased the chance of she respond with zero probability and decreased the probability value if she does not respond zero. The variable household income showed negative and significant effect on the dependent variable only for the first effect of the double- hurdle, while the dummy for whether the woman was at least his second marriage also showed a significant effect only for the first effect of double- hurdle, but a positive effect on the dependent variable.